Yritysten joukkorahoituskutsut genrehybrideinä koronapandemian ja Ukrainan sodan aikana - Maria Eronen-Valli (VAKKI Publications, 2023)
Crowdfunding campaigns are a form of digital fundraising in which anyone can participate as a supporter (backer). The central genre of crowdfunding is campaign call, that is, a fundraising-oriented pitch published on a crowdfunding platform. This study focuses on crowdfunding campaign calls in times of two world-wide crises: Ukrainian war and Covid pandemic. The aim of the study is to find out what kinds of hybrid genres crisis-contextualized crowdfunding campaign calls are. The material of the study consists of 67 successful business-oriented campaign calls, 27 of which are from Ukrainian companies fundraising on Kickstarter during the Ukrainian war, while 20 Mesenaatti campaign calls belong to Finnish and 20 Indiegogo calls mainly to U.S. companies suffering from the Covid pandemic. The study utilizes Rhetorical Genre Studies (RGS) and approaches crowdfunding campaign calls as mixtures or combinations of characteristics from several genres. The study discusses the five most typical genres found in the data: 1) entrepreneurial narrative, 2) advertisement, 3) conditions of contract and delivery, 4) project plan, and 5) political statement. The results indicate that in times of societal crises, crowdfunding campaign calls mix emotion-evoking storytelling and political stance-taking with more rational types, such as product information (a type of advertising) and project plan.